Holter monitoring in dogs: 24 h vs. 48 h. (June 2021) - Mavropoulou, A.; Oliveira, P.; Willis, R.
Highlights: Holter monitoring in dogs is useful for the detection and assessment of arrhythmias. In 25% of cases, Holter diagnosed an arrhythmia that caused clinical signs. A 48 h Holter increased the likelihood of documenting an arrhythmia during an event. A 48 h Holter only slightly increased the likelihood of identifying an arrhythmia. Abstract: Holter monitoring has an important role in the diagnosis of cardiac arrhythmias in dogs with underlying heart disease or clinical signs such as intermittent weakness/ collapse or exercise intolerance, and in the assessment of antiarrhythmic treatment efficacy. A typical recording lasts for 24 h, although 48 h or any number of days up to 7 are possible, especially when investigating clinical signs that may not happen during the first 24 h. The objective of this study was to review retrospectively a large number of 48 h Holter recordings obtained from dogs to assess the possible incremental diagnostic yield of the second 24 h period in comparison to the first 24 h. Three hundred and fifty four 48 h Holter recordings were included in the study for analysis. A 48 h Holter recording contributed to a 14.5% increase in the likelihood of documenting the cardiac rhythm during an event of interest; a 24 h recording increased the diagnostic yield from 32.2% to 46.7%. When the recordings were grouped according to the most important rhythm abnormalities (supraventricular arrhythmias group, ventricular arrhythmias group, bradyarrhythmias group, no arrhythmias group), the 48 h Holter monitor contributed to a 5% increase in the likelihood of identifying a relevant cardiac rhythm abnormality, increasing the diagnostic yield from 58% to 63%. This benefit occurred mostly in dogs with iterative or paroxysmal supraventricular arrhythmias. In dogs with bradyarrhythmias or ventricular arrhythmias, an additional 24 h of analysis was useful in only a limited number of cases.